2018
DOI: 10.1371/journal.pone.0203663
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of future consequences (CFC) serves as a buffer against aggression related to psychopathy

Abstract: Psychopathy is the most notorious trait in the Dark Triad, and it is strongly linked to many kinds of aggressive behaviors. However, not every individual who is characterized by psychopathy engages in aggression, which suggests that certain factors may attenuate the intensity of the relations between psychopathy and aggression. The purpose of the current study was to explore the protective roles of the consideration of future consequences (CFC) (high CFC-Future and low CFC- Immediate) in attenuating aggression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…As expected, the longitudinal relationship between angry rumination and proactive aggression was moderated by CFC-I. The results mentioned above are consistent with the previous study which indicated that CFC served as a buffer against aggression related to psychopathy (Zhao et al, 2018).…”
Section: The Relationship Between Angry Rumination and Proactive Agsupporting
confidence: 91%
See 1 more Smart Citation
“…As expected, the longitudinal relationship between angry rumination and proactive aggression was moderated by CFC-I. The results mentioned above are consistent with the previous study which indicated that CFC served as a buffer against aggression related to psychopathy (Zhao et al, 2018).…”
Section: The Relationship Between Angry Rumination and Proactive Agsupporting
confidence: 91%
“…After the translated and retranslated version, as well as the original English versions were compared and discussed, the finalized version of Chinese CFCS was completed. The Chinese version had been used in a prior study and was found to have adequate reliability and validity (Zhao, Wei, Chen, & Xia, 2018). In addition, a CFA with random item parceling was administrated to test the structure validity of the subscale in a larger sample ( N = 942).…”
Section: Studymentioning
confidence: 99%
“…According to socioemotional selectivity theory, different feelings about future events were thought to influence near or far future goal setting, which makes college students consider the consequence of futures with different distances (Chen, 2006;Lang & Carstensen, 2002;Lyu & Huang, 2016). The consideration of future consequences (CFC) refers to the cognition of distant future consequences (Strathman et al, 1994;Zhao et al, 2018). The mental time of the future can be classified into the near future and the far future (Chen, 2006).…”
Section: Consideration Of Future Consequences As a Mediatormentioning
confidence: 99%
“…Some people are more likely to act to satisfy immediate concerns, while some people are more likely to pursue a sequence of better far future outcomes, such as demand satisfaction and economic benefits, even though immediate happiness may be sacrificed (Joireman et al, 2008). Considering immediate consequences (CFC-immediate) and future consequences (CFC-future) are the two major components of CFC (Joireman et al, 2008;Zhao et al, 2018). CFC-immediate emphasizes a focus on immediate future consequences, while CFC-future focuses on far future consequences.…”
Section: Consideration Of Future Consequences As a Mediatormentioning
confidence: 99%
“…People frequently face a dilemma between short-term and long-term interests in their attitudes and behaviors, for example, for risk-taking [ 27 ], health behavior such as engaging in exercise or eating healthily [ 28 ], pro-environmental behavior and sustainability [ 29 , 30 ], aggressiveness [ 31 , 32 ], and delinquent behavior [ 33 ], as well as in financial investment decisions [ 34 , 35 ]. In general, in these kinds of temporal dilemmas, pursuing future goals (e.g., performing well in exams [ 36 ]) involves self-control: it is important not to give in to the alluring, but, in the long run, hindering, hedonistic activities in the present.…”
Section: Introductionmentioning
confidence: 99%